2005
DOI: 10.1055/s-2004-830558
|View full text |Cite
|
Sign up to set email alerts
|

Six-Minute Walking Test to Assess Exercise Tolerance and Cardiorespiratory Responses During Training Program in Children With Congenital Heart Disease

Abstract: This study assessed the exercise tolerance and the cardiorespiratory responses to a training program by the six-minute walk test (6'WT) in children with congenital heart disease (CHD). Seventeen cardiac and 14 healthy children performed maximal cardiopulmonary exercise test (CPET) and 6'WT. Reliability of 6'WT was assessed in all subjects (test-retest) by Bland-Altman plots. Cardiac subjects were randomly divided in training (T-CHD) and control groups (C-CHD). T-CHD underwent an individualized training exercis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
57
0
15

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(81 citation statements)
references
References 20 publications
(30 reference statements)
9
57
0
15
Order By: Relevance
“…The boys walked 564.9 ± 53.7 m, whereas the girls walked 506.7 ± 55.0 m. Similar walking performance has been reported in previous studies in children. 15,19 The difference between boys and girls could be due to metabolic abnormalities and anthropometric factors, which are usually independently associated with the distance walked. 31 In the present study, we present regression models that allow the evaluator to estimate FATmax for obese children of both genders.…”
Section: Discussionmentioning
confidence: 99%
“…The boys walked 564.9 ± 53.7 m, whereas the girls walked 506.7 ± 55.0 m. Similar walking performance has been reported in previous studies in children. 15,19 The difference between boys and girls could be due to metabolic abnormalities and anthropometric factors, which are usually independently associated with the distance walked. 31 In the present study, we present regression models that allow the evaluator to estimate FATmax for obese children of both genders.…”
Section: Discussionmentioning
confidence: 99%
“…In adult cardiac patients after myocardial infarction (MI), it has been shown that the confidence of the patient and their spouse can be significantly improved when a CPET is performed three weeks after the MI. 9 Lastly, CPET (as well as field tests, such as the 6-minute walk test 10 ) can be used to show improvement of physical rehabilitation in children with CHD. Furthermore, a fitness assessment including CPET can be helpful in motivating children with CHD to maintain a healthy body weight or to combat overweight/ obesity.…”
Section: Contraindications For Exercise Testingmentioning
confidence: 99%
“…En población adulta existen múltiples estudios publicados que han permitido establecer valores normales [11][12][13][14] . En pediatría ha sido utilizado en niños sanos [4][5][6]9,10,15 , en pacientes con fibrosis quística 7,8 , bronquiolitis obliterante 16 , cardiopatías y trasplantes cardiacos y/o pulmonares, así como también, en intervenciones terapéuticas 17 . Sin embargo, aún sigue siendo poco utilizado en población pediátrica y la falta de valores de referencia ha dificultado su interpretación.…”
unclassified